2021
DOI: 10.3390/catal11101223
|View full text |Cite
|
Sign up to set email alerts
|

Rh-Catalyzed Reductive Amination of Undecanal in an Aqueous Microemulsion System Using a Non-Ionic Surfactant

Abstract: The homogeneously catalyzed reductive amination of the long-chain aldehyde undecanal with diethylamine was performed in an aqueous microemulsion system using the non-ionic surfactant Marlophen NP8. The experiments showed that the used water-soluble rhodium/SulfoXantphos catalyst system is suitable for this reaction. The Rh-catalyzed formation of the alcohol by-product can be completely suppressed by the use of carbon monoxide with its stabilizing effect of the catalyst system. In addition to pressure and tempe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
34
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(37 citation statements)
references
References 23 publications
(26 reference statements)
3
34
0
Order By: Relevance
“…This effect of carbon monoxide on the suppression of alcohol formation has already been observed in the literature. 2,6 Given that the CO addition had a much more significant influence than a reduction of catalyst concentration, it can be concluded that the CO does not act by partially deactivating the catalyst but rather by changing the catalyst species, which can also be observed by the color change of the catalyst solution from red (without CO) to yellow (with CO); see SI for photos.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…This effect of carbon monoxide on the suppression of alcohol formation has already been observed in the literature. 2,6 Given that the CO addition had a much more significant influence than a reduction of catalyst concentration, it can be concluded that the CO does not act by partially deactivating the catalyst but rather by changing the catalyst species, which can also be observed by the color change of the catalyst solution from red (without CO) to yellow (with CO); see SI for photos.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…The hydroaminomethylation experiments were carried out in a 100 mL stainlesssteel reactor (Halmosi GmbH, Heilbronn, Germany). A detailed experimental setup has already been published and can be found in the literature [17]. The solvents water and dodecane, the surfactant, and the sodium sulfate were added to the reactor, evacuated for 5 min, and flushed with nitrogen.…”
Section: Procedures For the Hydroaminomethylation Experimentsmentioning
confidence: 99%
“…The catalyst recycling for the HAM was performed exactly as described in our paper on reductive amination [17]: a typical reaction mixture for the hydroaminomethylation was prepared (21.4 mmol 1-decene, 21.4 mmol DEA, 9 g dodecane, 12 g water, 0.23 mol% Rh(acac)(cod), 0.92 mol% SX, 8 wt% Marlophen NP8, 1 wt% Na 2 SO 4 ). The first run was performed for 2 h (30 bar synthesis gas, 120 • C) and cooled down to 50 • C for reaction gas releasing.…”
Section: Catalyst Recyclingmentioning
confidence: 99%
See 1 more Smart Citation
“…These aggregates are able to solubilize otherwise insoluble compounds. These “green” surfactant solvent systems have gained increased attention in the chemical and biochemical industry and in addition to other applications, are capable to be applied in the hydroformylation of long-chain olefins to aldehydes and the subsequent reductive amination to amines. In terms of the surfactants used, especially nonionic poly­(ethylene oxide) alkyl ether surfactants are of interest due to their readily modifiable hydrophilic and hydrophobic properties . These surfactants consist of an alkyl chain as the hydrophobic tail, and an ethylene oxide chain as the hydrophilic head.…”
Section: Introductionmentioning
confidence: 99%